Halogen-free flame-retardant sheath material for low-voltage power cable and preparation method thereof

CN122810487APending Publication Date: 2026-09-25JIANGSU ZHONGMEI CABLE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611298488.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

[0004]然而,上述现有技术仍存在明显的性能短板:其配方体系围绕阻燃性能展开优化,并未关注护套的导热散热能力,传统聚烯烃基体与高填充无机阻燃剂构成的体系导热系数普遍偏低,电缆导体通电产生的焦耳热难以通过护套快速向外散发,导致电缆内部持续温升,既加速绝缘层热氧老化、缩短使用寿命,也限制了电缆的实际载流能力;若在现有体系中直接引入导热填料以改善散热,则会进一步稀释阻燃组分、破坏炭层连续性,导致阻燃效率下降、烟密度升高,形成导热散热性能与阻燃性能相互制约的技术瓶颈,难以同时满足低压电力电缆运行散热提载与消防阻燃安全的双重核心需求

Benefits of technology

1、本申请通过引入β-环糊精接枝聚硅氧烷作为阻燃协效组分,有效突破了传统氢氧化物无卤阻燃体系效率偏低、依赖超高填充的技术局限。针对现有无卤护套料中阻燃填充量升高易引发力学性能劣化、加工难度增大,且挤占功能组分分散空间的共性问题,该协效组分可从凝聚相层面强化阻燃作用:环糊精结构单元可在燃烧前期快速脱水炭化,为炭层形成提供有机碳骨架;聚硅氧烷链段可向材料表面迁移富集,与氢氧化物分解产物协同构建致密连续的硅氧炭质阻隔层。二者与氢氧化铝、氢氧化镁复配后,可显著提升单位填充量的阻燃效率,在满足阻燃等级要求的前提下避免超高填充,为导热功能组分的引入预留基体空间,同时缓解高填充体系的加工流动阻力,从阻燃效率层面化解了填充量与材料性能之间的固有矛盾。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the technical field of high polymer materials, and particularly discloses a halogen-free flame-retardant sheath material for low-voltage power cables and a preparation method thereof. The halogen-free flame-retardant sheath material for low-voltage power cables is prepared from the following raw materials in parts by weight: 40-50 parts of ethylene-vinyl acetate copolymer, 5-10 parts of polyolefin elastomer, 20-25 parts of linear low-density polyethylene, 5-8 parts of maleic anhydride grafting compatibilizer, 80-100 parts of aluminum hydroxide, 40-60 parts of magnesium hydroxide, 1-3 parts of silane coupling agent, 0.8-1.2 parts of zinc stearate, 1-2 parts of antioxidant, 0.5-1 part of stabilizer, 2-6 parts of beta-cyclodextrin grafted polysiloxane and 1-4 parts of nano boron nitride@polydopamine core-shell particles. The sheath material of the application can meet the halogen-free low-smoke flame-retardant requirement, significantly improve the heat conduction and heat dissipation capacity, effectively reduce the internal temperature rise of the cable during operation, prolong the service life of the insulation layer and improve the current-carrying capacity of the cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polymer materials technology, and more specifically, it relates to a halogen-free flame-retardant sheathing material for low-voltage power cables and its preparation method. Background Technology

[0002] As the outermost protective material of power cables, cable sheathing materials undertake multiple functions, including mechanical protection, environmental resistance, and electrical insulation. Their performance directly determines the service life and operational safety of the cable. With the continuous improvement of urban power grid construction and building electrification in my country, the application scale of low-voltage power cables in densely populated places such as high-rise buildings, rail transit, and data centers is constantly expanding. The industry's requirements for the environmental protection and fire safety of sheathing materials are becoming increasingly stringent. Traditional polyvinyl chloride (PVC) sheaths, due to the release of large amounts of halogen acid toxic gases and corrosive fumes during combustion, have been gradually replaced by low-smoke halogen-free flame-retardant polyolefin sheathing materials. However, halogen-free flame-retardant systems based on aluminum hydroxide and magnesium hydroxide require high filler content to achieve flame-retardant standards, often leading to problems such as decreased material mechanical properties and increased processing difficulty. At the same time, the contradiction of insufficient thermal conductivity of the sheath causing excessively high cable operating temperature rise and limited current carrying capacity is becoming increasingly prominent. Developing low-voltage cable halogen-free sheathing materials that combine excellent flame retardancy and smoke suppression, mechanical properties, and thermal conductivity has become a key research focus in the industry.

[0003] In the prior art, there have been many studies on the modification of low-smoke halogen-free cable sheath materials. For example, Chinese invention patent CN112662042B discloses a B1-grade low-smoke halogen-free cable sheath material and its preparation method. The raw materials of the B1-grade low-smoke halogen-free cable sheath material include linear low-density polyethylene resin, ethylene-octene copolymer, compatibilizer, flame retardant, smoke suppressant and charring agent, and processing aid. The smoke suppressant and charring agent is selected from a mixture of modified montmorillonite, nano-magnesium oxide, and nano-alumina. The flame retardant is selected from a mixture of aluminum hydroxide and magnesium hydroxide. This technical solution effectively improves the flame retardant rating through the synergistic effect of multiple flame retardant systems, and alleviates the contradiction between high filling and mechanical properties to a certain extent.

[0004] However, the aforementioned existing technologies still have significant performance shortcomings: their formulation systems are optimized around flame retardant performance but do not address the thermal conductivity and heat dissipation capacity of the sheath. The thermal conductivity of systems composed of traditional polyolefin matrices and highly filled inorganic flame retardants is generally low. The Joule heat generated by the cable conductor during power transmission is difficult to dissipate quickly through the sheath, leading to a continuous temperature rise inside the cable. This accelerates the thermal and oxidative aging of the insulation layer, shortens its service life, and limits the actual current carrying capacity of the cable. If thermally conductive fillers are directly introduced into the existing system to improve heat dissipation, it will further dilute the flame retardant components and disrupt the continuity of the char layer, resulting in a decrease in flame retardant efficiency and an increase in smoke density. This creates a technical bottleneck where thermal conductivity and flame retardant performance are mutually restrictive, making it difficult to simultaneously meet the dual core requirements of heat dissipation and load-bearing capacity for low-voltage power cables and fire-retardant safety. Summary of the Invention

[0005] In order to simultaneously improve the thermal conductivity and heat dissipation capacity and flame retardant and smoke suppression performance of cable sheaths, this application provides a halogen-free flame retardant sheath material for low-voltage power cables and its preparation method.

[0006] This application provides a halogen-free flame-retardant sheathing material for low-voltage power cables, which adopts the following technical solution: A halogen-free flame-retardant sheathing material for low-voltage power cables comprises the following raw materials in parts by weight: 40-50 parts of ethylene-vinyl acetate copolymer; 5-10 parts of polyolefin elastomer; 20-25 parts of linear low-density polyethylene; 5-8 parts of maleic anhydride graft compatibilizer; 80-100 parts of aluminum hydroxide; 40-60 parts of magnesium hydroxide; 1-3 parts of silane coupling agent; 0.8-1.2 parts of zinc stearate; 1-2 parts antioxidant; Stabilizer 0.5-1 part; 2-6 parts of β-cyclodextrin grafted with polysiloxane; 1-4 parts of boron nitride nanoparticles@polydopamine core-shell particles.

[0007] By adopting the above technical solution, this application uses a halogen-free flame retardant system composed of aluminum hydroxide and magnesium hydroxide, and introduces β-cyclodextrin-grafted polysiloxane as a synergistic functional component, overcoming the limitations of insufficient flame retardant efficiency of single hydroxides and the need to rely on ultra-high filler. Aluminum hydroxide and magnesium hydroxide achieve flame retardancy through multiple functions such as combustion endothermic reaction, release of water vapor to dilute combustible gases, and formation of an inorganic char layer. The combination of the two can exert a synergistic flame retardant effect in different temperature ranges. β-cyclodextrin-grafted polysiloxane has the dual functions of char source and smoke suppressant. The polyhydroxy cyclodextrin units in its molecular structure can be rapidly dehydrated and carbonized in the early stage of combustion, providing a carbon source for char layer formation. Meanwhile, the polysiloxane segments can migrate and accumulate on the material surface, participating in the construction of a dense and stable silicon-oxygen carbon protective layer, blocking the transfer of heat and oxygen, and inhibiting the release of smoke and combustible components. The synergistic effect of the two can significantly improve the char quality and flame retardant efficiency of the flame retardant system. Compared with the pure hydroxide flame retardant system without the addition of synergistic components, it can achieve the same flame retardant level with a lower total filling amount. It also reserves matrix dispersion space for the introduction of thermally conductive functional components, avoiding thermal conduction path obstruction and mechanical property deterioration caused by excessive filling of flame retardant fillers.

[0008] To address the technical bottlenecks in existing thermally conductive fillers where the introduction of easily diluted flame-retardant components disrupts the continuity of the char layer, this application achieves a balance between improved thermal conductivity and maintained flame-retardant performance by introducing nano-boron nitride@polydopamine core-shell particles. Nano-boron nitride itself possesses excellent thermal conductivity and insulation properties, enabling the construction of phonon transfer pathways within the matrix, effectively increasing the overall thermal conductivity of the sheath material and accelerating the dissipation of heat during cable operation. The polydopamine shell design, on the one hand, improves the interfacial compatibility between nano-boron nitride and the resin matrix through its abundant active functional groups, reducing interfacial thermal resistance and enhancing thermal conductivity at low filler contents. On the other hand, the polydopamine shell participates in the formation and reinforcement of the char layer during combustion, forming a positive synergy with the flame-retardant matrix system, rather than exhibiting the dilution effect of traditional thermally conductive fillers. The functional particles of this core-shell structure work together with β-cyclodextrin-grafted polysiloxane. The former constructs a thermally conductive network to improve heat dissipation efficiency, while the latter strengthens the carbon layer structure to ensure flame retardancy and smoke suppression. The two complement each other and work synergistically to fundamentally break the technical contradiction between thermal conductivity and flame retardancy.

[0009] Overall, in the technical solution of this application, each functional component of the sheath material system performs its own function while cooperating with each other: the matrix and compatibilizer ensure the mechanical and processing foundation; the hydroxide main flame retardant system provides basic flame retardant capability; β-cyclodextrin-grafted polysiloxane improves flame retardant and smoke suppression efficiency and optimizes processing performance; and nano-boron nitride@polydopamine core-shell particles construct thermally conductive pathways and assist in char formation. Ultimately, the sheath material meets the requirements of halogen-free, low-smoke flame retardancy while significantly improving thermal conductivity and heat dissipation, effectively reducing the internal temperature rise of the cable during operation, extending the service life of the insulation layer, and improving the current carrying capacity of the cable, while maintaining good mechanical properties and processing adaptability, making it suitable for the comprehensive use needs of low-voltage power cables in densely populated areas.

[0010] Optionally, the β-cyclodextrin-grafted polysiloxane is prepared by the following method: β-Cyclodextrin and carboxyl-terminated polysiloxane were added to anhydrous dichloromethane, and 4-dimethylaminopyridine and dicyclohexylcarbodiimide were added under stirring. The mixture was stirred and reacted at 20-40℃ for 24-48 h. After the reaction was completed, the mixture was filtered and dried under vacuum to obtain β-cyclodextrin-grafted polysiloxane.

[0011] By adopting the above technical solution, the above preparation method can form stable covalent chemical bonds between β-cyclodextrin and polysiloxane, avoiding the component migration and phase separation problems that are prone to occur in physical blending systems; at the same time, the grafted product completely retains the char-forming structure of β-cyclodextrin and the interface regulation characteristics of polysiloxane, so that it can be uniformly dispersed in the matrix and stably exert multiple functions of flame retardant synergy, internal lubrication and interface modification, ensuring the stable performance of the functional component.

[0012] Optionally, the mass ratio of the β-cyclodextrin, the carboxyl-terminated polysiloxane, and the anhydrous dichloromethane is 1:(2-6):(20-50).

[0013] Optionally, the amount of 4-dimethylaminopyridine added is 0.5%-2% of the total weight of β-cyclodextrin and carboxyl-terminated polysiloxane; the amount of dicyclohexylcarbodiimide added is 3%-10% of the total weight of β-cyclodextrin and carboxyl-terminated polysiloxane.

[0014] By adopting the above technical solution, the above raw material ratio can control the molecular structure and grafting degree of the grafted product, ensuring that the product has both sufficient char-forming active units and flexible siloxane segments; the reasonable amount of solvent can ensure the uniformity of the reaction system, avoid cross-linking side reactions caused by excessive local concentration, and ensure reaction efficiency, ultimately obtaining a grafted product with controllable structure and stable performance, providing a quality basis for its stable function in the sheath material.

[0015] Optionally, the boron nitride@polydopamine core-shell particles are prepared using the following method: Nano-boron nitride was dispersed in Tris-HCl buffer solution and ultrasonically dispersed for 20-30 min. Dopamine hydrochloride was added and the mixture was stirred at 25-30℃ for 8-12 h. After centrifugation, washing, and vacuum drying, nano-boron nitride@polydopamine core-shell particles were obtained.

[0016] By adopting the above technical solution, the above preparation method can introduce abundant active functional groups on the surface of boron nitride nanoparticles without destroying their intrinsic thermal conductivity. The polydopamine shell can not only improve the interfacial affinity between nanoparticles and polyolefin matrix, reduce interfacial thermal resistance, and improve the construction efficiency of thermal conductive network, but also participate in the construction of char layer during combustion, forming a synergistic effect with the flame retardant system. Structurally, it realizes the integrated design of thermal conductivity and flame retardant synergy.

[0017] Optionally, the mass ratio of the nano-boron nitride to the Tris-HCl buffer solution is 1:(20-30).

[0018] Optionally, the amount of dopamine hydrochloride added is 30%-50% of the weight of the nano boron nitride.

[0019] Optionally, the vinyl acetate content in the ethylene-vinyl acetate copolymer is 25wt%-40wt%.

[0020] By adopting the above technical solution, the content range of vinyl acetate in ethylene-vinyl acetate copolymer is limited. The appropriate vinyl acetate content can achieve a good balance between polarity, flexibility and processing fluidity of the matrix resin.

[0021] Optionally, the silane coupling agent is one of silane coupling agent KH-550 or silane coupling agent KH-560.

[0022] This application also provides a method for preparing halogen-free flame-retardant sheathing material for low-voltage power cables, using the following technical solution: A method for preparing a halogen-free flame-retardant sheath material for low-voltage power cables includes the following steps: S1: Dry aluminum hydroxide and magnesium hydroxide at 100-120℃ for 2-4 hours, cool them, and then stir them with silane coupling agent in a high-speed mixer at 80-100℃ for 10-20 minutes to obtain the modified flame retardant. S2: Ethylene-vinyl acetate copolymer, polyolefin elastomer, linear low-density polyethylene, maleic anhydride graft compatibilizer, zinc stearate, antioxidant, stabilizer, β-cyclodextrin grafted polysiloxane, nano boron nitride@polydopamine core-shell particles, and the modified flame retardant obtained in step S1 are added to a high-speed mixer and mixed evenly. Then, the mixture is fed into a twin-screw extruder for melt blending, extrusion granulation, and after extrusion, it is cooled, pelletized, and dried to obtain halogen-free flame-retardant sheath material for low-voltage power cables.

[0023] By adopting the above technical solution, the functional components can be uniformly dispersed in the matrix, ensuring the synergistic effect of the flame retardant system and the thermally conductive system is fully utilized. The process parameters are adapted to the thermal stability characteristics of the polyolefin matrix and the halogen-free flame retardant filler, avoiding the thermal decomposition failure of the functional components during processing. Moreover, the process is simple and controllable, suitable for industrial-scale production, and the resulting sheath material has uniform and stable performance.

[0024] In summary, this application has the following beneficial effects: 1. This application introduces β-cyclodextrin-grafted polysiloxane as a flame-retardant synergist, effectively overcoming the technical limitations of traditional hydroxide-based halogen-free flame-retardant systems, which suffer from low efficiency and reliance on ultra-high filler content. Addressing the common problems in existing halogen-free sheathing materials where increased flame-retardant filler content easily leads to mechanical property degradation, increased processing difficulty, and encroachment on the dispersion space of functional components, this synergist enhances the flame-retardant effect at the condensed phase level: the cyclodextrin structural units can rapidly dehydrate and carbonize in the early stages of combustion, providing an organic carbon skeleton for char layer formation; the polysiloxane segments can migrate and accumulate on the material surface, synergistically constructing a dense and continuous siloxane-carbon barrier layer with hydroxide decomposition products. When combined with aluminum hydroxide and magnesium hydroxide, the flame-retardant efficiency per unit filler content can be significantly improved, avoiding ultra-high filler content while meeting flame-retardant rating requirements. This reserves matrix space for the introduction of thermally conductive functional components and alleviates the processing flow resistance of high-filler systems, resolving the inherent contradiction between filler content and material performance from the perspective of flame-retardant efficiency.

[0025] 2. This application employs nano-boron nitride@polydopamine core-shell particles as the thermally conductive functional component, overcoming the technical bottleneck of the mutual constraint between thermal conductivity and flame retardant performance from a structural design perspective. Addressing the shortcomings of existing technologies where directly introducing thermally conductive fillers easily dilutes the flame-retardant components and disrupts the continuity of the char layer, leading to decreased flame-retardant efficiency and increased smoke density, this core-shell structure uses boron nitride as the core to construct a phonon transmission pathway, effectively improving the overall thermal conductivity of the sheath material, accelerating the outward dissipation of heat during cable operation, and reducing internal temperature rise. The polydopamine shell improves the interfacial affinity between the particles and the resin matrix, reducing interfacial thermal resistance and improving thermal conductivity at low filler content. Simultaneously, the polydopamine shell can participate in char layer construction and reinforcement during combustion, forming a positive synergy with the main flame-retardant system, rather than a simple dilution effect, achieving a harmonious balance between improved thermal conductivity and heat dissipation capacity and maintained flame-retardant and smoke-suppressing performance.

[0026] 3. This application achieves a comprehensive balance of flame retardant and thermal conductivity through a synergistic design of multi-component matrix compounding and multi-level interface regulation. Addressing the issues of increased interface defects, uneven component dispersion, and unbalanced overall performance that often occur in high-filler functional systems, this system uses ternary polyolefin resin as the continuous phase matrix. By complementing components with different crystallinity and polarity, it balances the material's rigidity, toughness, and processing fluidity. Furthermore, multi-level interface modification using maleic anhydride graft compatibilizers and silane coupling agents strengthens the interfacial bonding between the resin matrix and various inorganic fillers, reducing interface defects and ensuring the material's mechanical and electrical insulation properties. Based on this, flame-retardant synergistic components and thermally conductive functional particles can be uniformly dispersed and work synergistically within the matrix, enabling the sheath material to meet halogen-free, low-smoke, and flame-retardant safety requirements while also possessing excellent thermal conductivity and heat dissipation capabilities and good service adaptability, fully meeting the actual operational needs of low-voltage power cables. Detailed Implementation

[0027] The present application will be further described in detail below with reference to the embodiments.

[0028] Preparation example of β-cyclodextrin grafted polysiloxane Preparation Example 1 β-Cyclodextrin-grafted polysiloxanes were prepared using the following method: 1 kg of β-cyclodextrin and 2 kg of carboxyl-terminated polysiloxane were added to 20 kg of anhydrous dichloromethane. Stirring was started and the system temperature was maintained at 20 °C. After the raw materials were fully dispersed and dissolved, 15 g of 4-dimethylaminopyridine and 90 g of dicyclohexylcarbodiimide were added. The system was sealed and stirred continuously at 20 °C for 24 h. After the reaction was completed, the insoluble byproducts generated in the system were removed by filtration. The filtrate was concentrated under reduced pressure and precipitated with anhydrous ethanol. The solid product was collected by filtration again and dried in a vacuum drying oven at 60 °C to constant weight to obtain β-cyclodextrin-grafted polysiloxane.

[0029] Preparation Example 2 β-Cyclodextrin-grafted polysiloxanes were prepared using the following method: 1 kg of β-cyclodextrin and 4 kg of carboxyl-terminated polysiloxane were added to 35 kg of anhydrous dichloromethane. Stirring was started and the system temperature was maintained at 30 °C. After the raw materials were fully dispersed and dissolved, 62.5 g of 4-dimethylaminopyridine and 325 g of dicyclohexylcarbodiimide were added. The system was sealed and stirred continuously at 30 °C for 36 h. After the reaction was completed, the insoluble byproducts generated in the system were removed by filtration. The filtrate was concentrated under reduced pressure and precipitated with anhydrous ethanol. The solid product was collected by filtration again and dried in a vacuum drying oven at 60 °C to constant weight to obtain β-cyclodextrin-grafted polysiloxane.

[0030] Preparation Example 3 β-Cyclodextrin-grafted polysiloxanes were prepared using the following method: 1 kg of β-cyclodextrin and 6 kg of carboxyl-terminated polysiloxane were added to 50 kg of anhydrous dichloromethane. Stirring was started and the system temperature was maintained at 40 °C. After the raw materials were fully dispersed and dissolved, 140 g of 4-dimethylaminopyridine and 700 g of dicyclohexylcarbodiimide were added. The system was sealed and stirred continuously at 40 °C for 48 h. After the reaction was completed, the insoluble byproducts generated in the system were removed by filtration. The filtrate was concentrated under reduced pressure and precipitated with anhydrous ethanol. The solid product was collected by filtration again and dried in a vacuum drying oven at 60 °C to constant weight to obtain β-cyclodextrin-grafted polysiloxane.

[0031] Preparation example of boron nitride nanoparticles@polydopamine core-shell particles Preparation Example 4 Boron nitride nanoparticles@polydopamine core-shell particles were prepared using the following method: 1 kg of boron nitride nanoparticles were dispersed in 20 kg of Tris-HCl buffer solution and ultrasonically dispersed for 20 min. Then, 0.3 kg of dopamine hydrochloride was added, and the mixture was stirred at 25 °C for 8 h. After centrifugation, washing, and vacuum drying, boron nitride nanoparticles@polydopamine core-shell particles were obtained.

[0032] Preparation Example 5 Boron nitride nanoparticles@polydopamine core-shell particles were prepared using the following method: 1 kg of boron nitride nanoparticles were dispersed in 25 kg of Tris-HCl buffer solution and ultrasonically dispersed for 25 min. Then, 0.4 kg of dopamine hydrochloride was added, and the mixture was stirred at 28 °C for 10 h. After centrifugation, washing, and vacuum drying, boron nitride nanoparticles@polydopamine core-shell particles were obtained.

[0033] Preparation Example 6 Boron nitride nanoparticles@polydopamine core-shell particles were prepared using the following method: 1 kg of boron nitride nanoparticles were dispersed in 30 kg of Tris-HCl buffer solution and ultrasonically dispersed for 30 min. Then, 0.5 kg of dopamine hydrochloride was added, and the mixture was stirred at 30 °C for 12 h. After centrifugation, washing, and vacuum drying, boron nitride nanoparticles@polydopamine core-shell particles were obtained.

[0034] Example Example 1 A halogen-free flame-retardant sheathing material for low-voltage power cables, the raw material composition and formula of which are shown in Table 1, wherein the vinyl acetate content in the ethylene-vinyl acetate copolymer is 25wt%; the polyolefin elastomer is POE resin; and the weight average molecular weight of linear low-density polyethylene is 1.2×10⁻⁶. 5 The average particle size of aluminum hydroxide and magnesium hydroxide was 3 μm; the silane coupling agent was silane coupling agent KH-550, the antioxidant was antioxidant 1010; the stabilizer was calcium-zinc composite stabilizer; the β-cyclodextrin-grafted polysiloxane was the β-cyclodextrin-grafted polysiloxane prepared in Preparation Example 1; the boron nitride@polydopamine core-shell nanoparticles were the boron nitride@polydopamine core-shell nanoparticles prepared in Preparation Example 4.

[0035] A method for preparing a halogen-free flame-retardant sheath material for low-voltage power cables includes the following steps: S1: Aluminum hydroxide and magnesium hydroxide were dried at 100℃ for 2 hours, cooled, and then mixed with silane coupling agent in a high-speed mixer at 80℃ for 10 minutes to obtain a modified flame retardant. S2: Ethylene-vinyl acetate copolymer, polyolefin elastomer, linear low-density polyethylene, maleic anhydride graft compatibilizer, zinc stearate, antioxidant, stabilizer, β-cyclodextrin grafted polysiloxane, nano boron nitride@polydopamine core-shell particles, and the modified flame retardant obtained in step S1 are added to a high-speed mixer and mixed evenly. Then, the mixture is fed into a twin-screw extruder for melt blending, extrusion granulation, and after extrusion, it is cooled, pelletized, and dried to obtain halogen-free flame-retardant sheath material for low-voltage power cables.

[0036] Example 2 A halogen-free flame-retardant sheathing material for low-voltage power cables, the raw material composition and formula of which are shown in Table 1, wherein the vinyl acetate content in the ethylene-vinyl acetate copolymer is 30wt%; the polyolefin elastomer is POE resin; and the weight average molecular weight of linear low-density polyethylene is 1.2×10⁻⁶. 5 The average particle size of aluminum hydroxide and magnesium hydroxide was 3 μm; the silane coupling agent was silane coupling agent KH-560, the antioxidant was antioxidant 1010; the stabilizer was calcium-zinc composite stabilizer; the β-cyclodextrin-grafted polysiloxane was the β-cyclodextrin-grafted polysiloxane prepared in Preparation Example 2; the boron nitride nano@polydopamine core-shell particles were the boron nitride nano@polydopamine core-shell particles prepared in Preparation Example 5.

[0037] A method for preparing a halogen-free flame-retardant sheath material for low-voltage power cables includes the following steps: S1: Aluminum hydroxide and magnesium hydroxide were dried at 110℃ for 3 hours, cooled, and then mixed with silane coupling agent in a high-speed mixer at 90℃ for 15 minutes to obtain a modified flame retardant. S2: Ethylene-vinyl acetate copolymer, polyolefin elastomer, linear low-density polyethylene, maleic anhydride graft compatibilizer, zinc stearate, antioxidant, stabilizer, β-cyclodextrin grafted polysiloxane, nano boron nitride@polydopamine core-shell particles, and the modified flame retardant obtained in step S1 are added to a high-speed mixer and mixed evenly. Then, the mixture is fed into a twin-screw extruder for melt blending, extrusion granulation, and after extrusion, it is cooled, pelletized, and dried to obtain halogen-free flame-retardant sheath material for low-voltage power cables.

[0038] Example 3 A halogen-free flame-retardant sheathing material for low-voltage power cables, the raw material composition and formula of which are shown in Table 1, wherein the vinyl acetate content in the ethylene-vinyl acetate copolymer is 40wt%; the polyolefin elastomer is POE resin; and the weight average molecular weight of linear low-density polyethylene is 1.2×10⁻⁶. 5 The average particle size of aluminum hydroxide and magnesium hydroxide was 3 μm; the silane coupling agent was silane coupling agent KH-560, the antioxidant was antioxidant 1010; the stabilizer was calcium-zinc composite stabilizer; the β-cyclodextrin-grafted polysiloxane was selected from the β-cyclodextrin-grafted polysiloxane prepared in Preparation Example 3; the boron nitride nano@polydopamine core-shell particles were selected from the boron nitride nano@polydopamine core-shell particles prepared in Preparation Example 6.

[0039] A method for preparing a halogen-free flame-retardant sheath material for low-voltage power cables includes the following steps: S1: Aluminum hydroxide and magnesium hydroxide were dried at 120℃ for 4 hours, cooled, and then mixed with silane coupling agent in a high-speed mixer at 100℃ for 20 minutes to obtain a modified flame retardant. S2: Ethylene-vinyl acetate copolymer, polyolefin elastomer, linear low-density polyethylene, maleic anhydride graft compatibilizer, zinc stearate, antioxidant, stabilizer, β-cyclodextrin grafted polysiloxane, nano boron nitride@polydopamine core-shell particles, and the modified flame retardant obtained in step S1 are added to a high-speed mixer and mixed evenly. Then, the mixture is fed into a twin-screw extruder for melt blending, extrusion granulation, and after extrusion, it is cooled, pelletized, and dried to obtain halogen-free flame-retardant sheath material for low-voltage power cables.

[0040] Table 1. Raw material composition and proportions (kg) of halogen-free flame-retardant sheathing materials in Examples 1-3

[0041] Example 4 A halogen-free flame-retardant sheathing material for low-voltage power cables differs from Example 3 in that: in this example, the β-cyclodextrin-grafted polysiloxane is selected from the β-cyclodextrin-grafted polysiloxane prepared in Preparation Example 1; and the nano-boron nitride@polydopamine core-shell particles are selected from the nano-boron nitride@polydopamine core-shell particles prepared in Preparation Example 5.

[0042] Example 5 A halogen-free flame-retardant sheathing material for low-voltage power cables differs from Example 3 in that: in this example, the β-cyclodextrin-grafted polysiloxane is selected from the β-cyclodextrin-grafted polysiloxane prepared in Example 2; and the boron nitride@polydopamine core-shell nanoparticles are selected from the boron nitride@polydopamine core-shell nanoparticles prepared in Example 4.

[0043] Example 6 A halogen-free flame-retardant sheathing material for low-voltage power cables differs from Example 3 in that the vinyl acetate content in the ethylene-vinyl acetate copolymer in this example is 50wt%.

[0044] Comparative Example Comparative Example 1 A cable sheath material was prepared according to Example 1 in the patent document with publication number CN112662042B, entitled "A B1-grade low-smoke halogen-free cable sheath material and its preparation method".

[0045] Comparative Example 2 A halogen-free flame-retardant sheathing material for low-voltage power cables differs from Example 3 in that: β-cyclodextrin-grafted polysiloxane and nano-boron nitride@polydopamine core-shell particles were not added in this comparative example, and the difference was made up using ethylene-vinyl acetate copolymer.

[0046] Comparative Example 3 A halogen-free flame-retardant sheathing material for low-voltage power cables differs from Example 3 in that: in this comparative example, an equal amount of polysiloxane is used instead of β-cyclodextrin-grafted polysiloxane.

[0047] Comparative Example 4 A halogen-free flame-retardant sheathing material for low-voltage power cables differs from Example 3 in that: in this comparative example, an equal amount of nano-boron nitride is used instead of nano-boron nitride@polydopamine core-shell particles.

[0048] Performance testing The sheath material particles prepared in each embodiment and comparative example were placed in a flat vulcanizing machine and molded at 140°C and 10MPa pressure. They were then cut into test specimens of corresponding standard sizes and placed in a standard environment (23°C and 50% relative humidity) for 24 hours before performance testing.

[0049] 1. Thermal conductivity test Referring to GB / T10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Protective Hot Plate Method", the sample was made into a circular specimen with a diameter of 100 mm and a thickness of 5 mm. The thermal conductivity of the specimen at 25 °C was tested using the steady-state heat flow method. Three parallel specimens were tested in each group, and the arithmetic mean of the results was taken.

[0050] 2. Flame retardant performance test Limiting oxygen index: Refer to GB / T2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method - Part 2: Room temperature test", the sample size is 120mm×6.5mm×3mm, and the lowest oxygen volume fraction that the test sample can sustain combustion is recorded as the limiting oxygen index (LOI).

[0051] Vertical flammability rating: Refer to GB / T2408-2008 "Determination of flammability of plastics - Horizontal and Vertical Methods". The sample size is 125mm×13mm×3mm. The vertical flammability rating is evaluated based on the flaming time and dripping behavior.

[0052] 3. Smoke density performance test Referring to GB / T8323.2-2008 "Plastic Smoke Generation Part 2: Test Method for Determination of Smoke Density by Single Chamber Method", the maximum smoke density during the combustion process of the sample was tested using a smoke density test chamber, and the smoke density rating (SDR) was calculated. The smaller the value, the better the smoke suppression performance.

[0053] The performance test results of each embodiment and comparative example are shown in Table 2.

[0054] Table 2 Experimental Results

[0055] As shown in Table 2, the halogen-free flame-retardant sheathing material for low-voltage power cables prepared in this application embodiment achieves simultaneous improvement in both thermal conductivity and heat dissipation performance and flame-retardant and smoke-suppressing performance, effectively solving the technical bottleneck of mutual restriction between the two types of performance in the prior art. Among them, Example 3 has the best overall performance, with a thermal conductivity of up to 0.73 W / (m²). The limiting oxygen index (UOI) is 37.8%, the vertical combustion rating is V-0, and the smoke density rating is 42. Compared with Comparative Example 1, which represents the prior art, its thermal conductivity is increased by about 92%, while the limiting oxygen index is higher and the smoke density is lower, which fully demonstrates the advanced nature of the technical solution of this application.

[0056] In terms of thermal conductivity and heat dissipation, the thermal conductivity of each embodiment gradually increased with the increase of the amount of boron nitride nano@polydopamine core-shell particles added, and was significantly better than that of Comparative Example 2 without added thermally conductive components and Comparative Example 1 of the prior art. Comparing Example 3 and Comparative Example 4, it can be seen that the thermal conductivity of Comparative Example 4, which uses an equal amount of uncoated boron nitride nanoparticles, is only 0.55 W / (m²). K), which differs significantly from Example 3. The reason for this is that pure nano-boron nitride has poor interfacial compatibility with the polyolefin matrix, resulting in high interfacial thermal resistance and making it difficult to form a continuous phonon transport pathway; while the polydopamine shell can improve the interfacial affinity between the particles and the matrix, reduce interfacial heat loss, and enable the nanoparticles to build an efficient heat-conducting network with a lower filling amount, significantly improving the heat dissipation capacity of the sheath.

[0057] In terms of flame retardancy and smoke suppression, the vertical combustion rating of the samples in the examples with β-cyclodextrin-grafted polysiloxane all reached V-0, and the limiting oxygen index and smoke density were significantly better than those of Comparative Example 2 without this synergistic component. Comparing Example 3 and Comparative Example 3, it can be seen that after replacing the grafted product with pure polysiloxane, the limiting oxygen index of the samples decreased to 33.8%, the vertical combustion rating decreased to V-1, and the smoke density also increased significantly. This indicates that in β-cyclodextrin-grafted polysiloxane, the cyclodextrin units can provide a carbon source through dehydration and carbonization in the early stage of combustion, and the polysiloxane segments can migrate to the surface to construct a silicon-oxygen carbonaceous barrier layer. The two synergistically enhance the condensed phase flame retardant effect and improve the overall efficiency of the hydroxide flame retardant system, meeting flame retardant requirements without the need for ultra-high filler content.

[0058] Crucially, the thermally conductive functional component and the flame-retardant synergistic component in this application system achieve a positive synergistic effect, avoiding the contradiction common in conventional systems where "introducing thermally conductive fillers dilutes flame retardancy, while enhancing flame retardancy hinders thermal conductivity." On one hand, the polydopamine shell on the surface of nano-boron nitride can participate in the combustion and char formation process, working with β-cyclodextrin-grafted polysiloxane to improve the density of the char layer, thus offsetting the dilution effect of the thermally conductive filler on the flame-retardant system. On the other hand, the flame-retardant synergistic component improves flame-retardant efficiency, avoiding the need to further increase the amount of hydroxide filler to meet flame-retardant standards, and reducing the disruption and obstruction of the thermal conductivity pathway by a large amount of inorganic filler. This two-way synergy fundamentally breaks the performance constraint relationship between thermal conductivity and flame retardancy.

[0059] Furthermore, the performance differences between Examples 4 and 5 and Example 3 are small, indicating that the functional components obtained under different preparation parameters can function stably, and the preparation process has good controllability and repeatability. Overall, this application, through the structural design of functional components and the synergistic matching of multiple components, simultaneously upgrades the thermal conductivity and heat dissipation capacity and flame retardancy and smoke suppression level of the sheath material while maintaining its halogen-free and environmentally friendly properties. It also takes into account the basic mechanical and processing properties of the material, and can fully meet the dual requirements of heat dissipation and fire safety of low-voltage power cables.

[0060] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A halogen-free flame-retardant sheathing material for low-voltage power cables, characterized in that, The raw materials include the following parts by weight: 40-50 parts of ethylene-vinyl acetate copolymer; 5-10 parts of polyolefin elastomer; 20-25 parts of linear low-density polyethylene; 5-8 parts of maleic anhydride graft compatibilizer; 80-100 parts of aluminum hydroxide; 40-60 parts of magnesium hydroxide; 1-3 parts of silane coupling agent; 0.8-1.2 parts of zinc stearate; 1-2 parts antioxidant; Stabilizer 0.5-1 part; 2-6 parts of β-cyclodextrin grafted with polysiloxane; 1-4 parts of boron nitride nanoparticles@polydopamine core-shell particles.

2. The halogen-free flame-retardant sheathing material for low-voltage power cables according to claim 1, characterized in that, The β-cyclodextrin-grafted polysiloxane was prepared by the following method: β-Cyclodextrin and carboxyl-terminated polysiloxane were added to anhydrous dichloromethane, and 4-dimethylaminopyridine and dicyclohexylcarbodiimide were added under stirring. The mixture was stirred and reacted at 20-40℃ for 24-48 h. After the reaction was completed, the mixture was filtered and dried under vacuum to obtain β-cyclodextrin-grafted polysiloxane.

3. The halogen-free flame-retardant sheathing material for low-voltage power cables according to claim 2, characterized in that: The mass ratio of the β-cyclodextrin, carboxyl-terminated polysiloxane, and anhydrous dichloromethane is 1:(2-6):(20-50).

4. The halogen-free flame-retardant sheathing material for low-voltage power cables according to claim 2, characterized in that: The amount of 4-dimethylaminopyridine added is 0.5%-2% of the total weight of β-cyclodextrin and carboxyl-terminated polysiloxane; the amount of dicyclohexylcarbodiimide added is 3%-10% of the total weight of β-cyclodextrin and carboxyl-terminated polysiloxane.

5. The halogen-free flame-retardant sheathing material for low-voltage power cables according to claim 1, characterized in that, The boron nitride@polydopamine core-shell particles were prepared using the following method: Nano-boron nitride was dispersed in Tris-HCl buffer solution and ultrasonically dispersed for 20-30 min. Dopamine hydrochloride was added and the mixture was stirred at 25-30℃ for 8-12 h. After centrifugation, washing, and vacuum drying, nano-boron nitride@polydopamine core-shell particles were obtained.

6. The halogen-free flame-retardant sheathing material for low-voltage power cables according to claim 5, characterized in that: The mass ratio of the nano-boron nitride to the Tris-HCl buffer solution is 1:(20-30).

7. The halogen-free flame-retardant sheathing material for low-voltage power cables according to claim 5, characterized in that: The amount of dopamine hydrochloride added is 30%-50% of the weight of nano boron nitride.

8. The halogen-free flame-retardant sheathing material for low-voltage power cables according to claim 1, characterized in that: The vinyl acetate content in the ethylene-vinyl acetate copolymer is 25wt%-40wt%.

9. The halogen-free flame-retardant sheathing material for low-voltage power cables according to claim 1, characterized in that: The silane coupling agent is one of silane coupling agent KH-550 or silane coupling agent KH-560.

10. A method for preparing a halogen-free flame-retardant sheath material for low-voltage power cables according to any one of claims 1-9, characterized in that, Includes the following steps: S1: Dry aluminum hydroxide and magnesium hydroxide at 100-120℃ for 2-4 hours, cool them, and then stir them with silane coupling agent in a high-speed mixer at 80-100℃ for 10-20 minutes to obtain the modified flame retardant. S2: Ethylene-vinyl acetate copolymer, polyolefin elastomer, linear low-density polyethylene, maleic anhydride graft compatibilizer, zinc stearate, antioxidant, stabilizer, β-cyclodextrin grafted polysiloxane, nano boron nitride@polydopamine core-shell particles, and the modified flame retardant obtained in step S1 are added to a high-speed mixer and mixed evenly. Then, the mixture is fed into a twin-screw extruder for melt blending, extrusion granulation, and after extrusion, it is cooled, pelletized, and dried to obtain halogen-free flame-retardant sheath material for low-voltage power cables.

Citation Information

Patent Citations

  • A B1 grade low-smoke halogen-free cable sheath material and its preparation method

    CN112662042B